(untitled) (Perspectivas em Ciência da Informação, 2008)
Abstract: Lack of theoretical bases and sound methodologies are problems that arise when building Ontologies. The study proposes systematization of relations found in the the literature from Information Science, Terminology, Computer Science and Bioinformatics. The systematization proposed aims at linking couple of categories (categorical relations) with relations properly (formal relations). The study shows that different relations may arise in different domains and that systematic definitions are fundamental for the establishment of formal relations.